Multiscale mechanical fatigue damage of stainless steel investigated by neutron diffraction and X-ray microdiffraction. (15th February 2019) - Li, Runguang; Wang, Yan-Dong; Liu, Wenjun; Geng, Chang; Xie, Qingge; Brown, Dennis E.; An, Ke
Abstract: Mechanical fatigue behavior of AL6XN stainless steel as a typical type of planar slip alloy was investigated by in situ neutron diffraction and synchrotron-based X-ray microdiffraction methods. Under cyclic loading at a high strain amplitude (±0.8%), the fatigue damage originated mainly from the accumulation of statistical stored dislocations, as clearly evidenced from a continuous increase in diffraction peak width with increasing the number of load cycles. However, under cyclic loading at a low strain amplitude (±0.3%), the density of statistical stored dislocations became saturated just after a hundred loading cycles and the fatigue damage was mainly dominated by the accumulation of persistent Lüders bands (PLBs) and the complex interactions among various PLBs as evidenced through X-ray microdiffraction measurements. It was further found that there exists obvious grain-orientation-dependent local damage in the low-strain-amplitude fatigued sample. In particular, fatigued grains orientated with [001] paralleling the loading direction are subjected to compressive stress and contain a large number of broad PLBs in boundaries arraying the edge dislocation pile-ups, which generate a large stress gradient leading to local plastic instability. The highly localized stress field at PLBs in the cyclically-deformed sample at a low strain amplitude may explain the obvious cyclic stress softening. Graphical abstract: Image 1